Green HRM : a climate-conscious route to triple bottom line - Agrawal, Soni; Puri, Roma (New Delhi Sage, 2021)
"HR's strategic role in an organisation can help save the planet while driving profits for the company! Do organizations see sustainability as a solo initiative of a department to fulfil statutory requirements or is it an investment towards the well-being of people, planet and profitability? If so, then how important is the contribution of HR towards the greening of an organization? The book is an industrious guide on Green HRM and sustainability practices towards fulfilling the three-pronged goals of triple bottom line. Through the success stories of employees as change agents, it showcases how Green HRM can mesh sustainability with strategy by linking organizational factors such as vision and mission, leadership, organizational culture and employees' pro-environmental attitude with the organization's profit goals. 'A timely book when the entire world is experiencing the coronavirus pandemic.' -Mussarat Hussain, Head, Leadership & Functional School, Maruti Suzuki"--
Keywords: Social responsibility of business